Impact of the Protection Factor on the Family Economy on the Sustainability of Private Educational Companies - Vilela-Rodriguez, Magali (Journal of Ecohumanism, 2024)
A systematic review of the academic production on Family Economics and Educational Enterprises was carried out, according to the PRISMA model (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The purpose of this analysis was to analyze the main characteristics of the publications indexed in the databases of the science indexing networks Scopus and WoS, in addition to their scope in the treatment of the proposals of the variables. In turn, we started with a list of 35 publications, which were refined with the use of the following keywords in the search engines of the two indexing networks mentioned, FAMILY ECONOMY AND EDUCATIONAL ENTERPRISES. Once the duplication documents were eliminated, using inclusion-exclusion criteria, a total of 12 studies were selected for final analysis. The findings show that families with financial stability are a determining factor in ensuring that private educational companies sustain themselves. Securing their sources of financing, through their diversification, together with implementing sustainable business models, are of special attention to ensure their continuity in the face of economic fluctuations.